A Semantic Analysis of Taylor Swift's Songs: Leech's Seven Types Meaning - Kholilah Yuniar Nasution; Lismawarni; Mesra Sinambela; Dina Puspitra Sari Daulay (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Background: The abstract doesn't explicitly state a specific problem. It focuses on exploring the semantic richness of Taylor Swift's lyrics. Purpose: To identify and elucidate the different types of meaning embedded within Taylor Swift's song lyrics and understand how these meanings contribute to the overall emotional and thematic expression of the songs. Design/methods/approach: A descriptive qualitative approach, analyzing the lyrics of Taylor Swift's most popular songs based on Spotify records in 2024, using Geoffrey Leech’s theory of the seven types of meaning. Findings: Affective meaning is the most dominant type in Swift’s songs, In the song "Fortnight," affective meaning constitutes 25% of the analyzed lyrics, Taylor Swift’s lyrics are characterized by a rich semantic texture, where emotional and conceptual meanings interplay. Research implications/limitations: The abstract doesn't explicitly mention limitations. However, a potential implication is that the findings contribute to a broader understanding of how contemporary song lyrics function as a medium for complex emotional and thematic communication. Originality/value: The abstract suggests the study offers new insights into Taylor Swift's lyrical artistry by applying Leech's semantic framework. It also implies a contribution to the field of semantics by analyzing how meaning is constructed in contemporary song lyrics.